The gastric sieve of penaeid shrimp species is a sub-micrometer nutrient filter - Werawich Pattarayingsakul (2020)
© 2019. Published by The Company of Biologists Ltd. Unlike that of vertebrates, the penaeid shrimp stomach is of ectodermic origin and is thus covered by a cuticle that is sloughed upon molting. It is composed of two chambers, here called the anterior and posterior stomach chambers, ASC and PSC, respectively. The PSC contains a filtration structure variously called a pyloric filter, filter press, gastric filter or gastric sieve (GS), and the last of these will be used here. The GS resembles an elongated, inverted-V, dome-like, chitinous structure with a midline ridge that is integral to the ventral base of the PSC. The dome surface is covered with a carpet-like layer of minute, comb-like setae bearing laterally branching setulae. This carpet serves as a selective filter that excludes large partially digested food particles but allows smaller particles and soluble materials to enter hepatopancreatic ducts that conduct them into the shrimp hepatopancreas (HP), where further digestion and absorption of nutrients takes place. Although the GS function is well known, its exclusion limit for particulate material has not been clearly defined. Using histological and ultra-structure analysis, we show that the GS sieve pore diameter is approximately 0.2–0.7 µm in size, indicating a size exclusion limit of substantially less than 1 µm. Using fluorescent microbeads, we show that particles of 1 µm diameter could not pass through the GS but that particles of 0.1 µm diameter did pass through to accumulate in longitudinal grooves and move on to the HP, where some were internalized by tubule epithelial cells. We found no significant difference in these sizes between the species Penaeus monodon and Penaeus vannamei or between juveniles and adults in P. vannamei. This information will be of value for the design of particulate feed ingredients such as nutrients, therapeutic drugs and toxin-absorbing materials that may selectively target the stomach, intestine or HP of cultivated shrimp.